Woman's world/Woman's empire : the Woman's Christian Temperance Union in international perspective, 1880-1930 - Tyrrell, Ian R. (University of North Carolina Press, 1991)
Woman's World/Woman's Empire: The Woman's Christian Temperance Union in International Perspective, 1880-1930.